(x+400000)+x=600000000

Simple and best practice solution for (x+400000)+x=600000000 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+400000)+x=600000000 equation:


Simplifying
(x + 400000) + x = 600000000

Reorder the terms:
(400000 + x) + x = 600000000

Remove parenthesis around (400000 + x)
400000 + x + x = 600000000

Combine like terms: x + x = 2x
400000 + 2x = 600000000

Solving
400000 + 2x = 600000000

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-400000' to each side of the equation.
400000 + -400000 + 2x = 600000000 + -400000

Combine like terms: 400000 + -400000 = 0
0 + 2x = 600000000 + -400000
2x = 600000000 + -400000

Combine like terms: 600000000 + -400000 = 599600000
2x = 599600000

Divide each side by '2'.
x = 299800000

Simplifying
x = 299800000

See similar equations:

| 9(x-5)-2=-47 | | (9/4)x+1 | | -x=56 | | x+(x+32)+(2x-33)=751 | | 9(t-5)+5t=7(2t+4)-12 | | (x+1)(x+4)=40 | | (x+16)+x=364 | | (x+16)x=364 | | 19m-1=2 | | -2(5s-2)-4=-3(8s+2)-3 | | -(1/6)(x-18)+(1/3)(x+3)=x+14 | | 3x=19.2 | | x^2-8x-75=0 | | x^2-8x+75=0 | | 10=x^2+7x | | N+55=128 | | -(1/6)(x-18)+(1/3)(x+3)=x-11 | | -8/5x=96 | | 8-(2x-6)=4-3x | | 9x^4+12x^3+4x^2+1=0 | | 2x+6=-11 | | (19/30)x+4=(7/10)x | | 4(-5m-3)+2m= | | 2z^8a^8/z^7a^3 | | (19/30)x=(7/10)x | | -7+4(3-2p)= | | 7+19t-5=9t+62-2t | | 10x+4=5+2x | | 5(-6+4h)= | | 4x+13y=60 | | -2k-4-5+6k= | | -4(7p+9)= |

Equations solver categories